Impact of Capital Structure on Bank Financial Performance of Al Ahli Bank in Saudi Arabia (Global Journal of Management and Business Research, 2015)
This paper seeks to examine the relationship between capital structure and bank financial performance. This research had verified the existence of several negative relationships between capital structure (accumulated capital and annual investments) and strategic financial performance, while finding mixed results for the relationship between capital structure (accumulated capital and annual investments) and profitability.
Keywords: capital structure; bank performance; ROA; ROE; EPS